2019
DOI: 10.18805/ijar.b-3690
|View full text |Cite
|
Sign up to set email alerts
|

Studies on linear body measurements of gaolao calves in the breeding tract of Maharashtra

Abstract: The body measurement and body weight of Gaolao calves at various stages of growth were studied for both male and female at different location in the breeding tract. The idea is to obtain the real picture of the breed in the breeding tract. The body measurements play an important role in judging calves and often help in predicting probable value of the calves. Body length and height at wither are the measures of bone growth while chest girth is measures of development of muscles, bone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…et al, 2019). Again, Wagh, et al (2019) reported 31.24 ± 0.62 kg body weights at 0-3 months of age for Gaolao calves of Maharashtra.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…et al, 2019). Again, Wagh, et al (2019) reported 31.24 ± 0.62 kg body weights at 0-3 months of age for Gaolao calves of Maharashtra.…”
Section: Resultsmentioning
confidence: 95%
“…Effect of Sex on the Body Weights of Pure Breed Sahiwal Calf under the High Humid Conditions of Assam revealed non-significant effect of sex on body weight of Red Kandhari calves at 0-3 months of age but highly significant (P<0.01) effect of sex at 4-6 months of age. Wagh, et al (2019) revealed that least squares mean for body weight of Gaolao calves for male and female calves were 32.19 ± 0.85 kg and 30.30 ± 0.89 kg respectively. The least squares analysis of variance revealed non-significant effect of sex on body weight of Gaolao calves at 0-3 months of age.…”
Section: Discussionmentioning
confidence: 96%